2019
DOI: 10.3390/environments6040047
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Generating Electricity Using Small-Scale Wind Turbines and Solar Photovoltaic Systems for Households in Northern Cyprus: A Comparative Study

Abstract: The increased energy demand and related environmental problems caused by burning fossil fuels have raised interest in alternative energy sources. This study investigated the wind characteristics and available wind energy for three urban regions in Northern Cyprus using the Weibull distribution function. The results illustrate that Gazimağusa is the most applicable location for harvesting the kinetic energy of the wind compared to Lefkoşa and Girne. Moreover, the solar potential at a specific location can be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Studies on renewable energy sources in the northern part of Cyprus, show that the solar and wind potential is intensively investigated, Table 2 . Climatic conditions make the installation of solar and wind power plants ideal in the country, but the potential and efficiency of solar energy in NC is much more important than wind energy [ 20 , 21 , 22 ]. In NC, there are not yet large platforms where wind turbines are installed that allow the use of wind energy.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on renewable energy sources in the northern part of Cyprus, show that the solar and wind potential is intensively investigated, Table 2 . Climatic conditions make the installation of solar and wind power plants ideal in the country, but the potential and efficiency of solar energy in NC is much more important than wind energy [ 20 , 21 , 22 ]. In NC, there are not yet large platforms where wind turbines are installed that allow the use of wind energy.…”
Section: Methodsmentioning
confidence: 99%
“…The performance of the 6.4 kWp gridconnected rooftop PV system is evaluated using three types of simulation software (PVGIS, PV*SOL, and PVWatts) and the effects concluded that PVGIS is an easy, fast, and dependable software program device that may be used for the simulation of a sun PV machine to the studied regions. 40 The hybrid system is sized to meet Jordan's renewable energy rules by maximizing the proportion of demand satisfied by the hybrid system (FRES) with the cost of electricity less than the grid tariff and a 100% renewable energy ratio. In addition to, the technical and economic viability, the integrated lithium-ion bank batteries are investigated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Propose a 4.85 kW grid-connected PV rooftop systems in Nicosia (Lefkoşa), Morphou (Güzelyurt) and Dipkarpaz All selected locations have a higher potential for solar energy [40] Develop a 6.4 kW grid-connected PV wind systems for household in Lefkoşa, Girne and Gazima gusa…”
Section: Reference Year Description/aimmentioning
confidence: 99%